Efficacy of Low-Dose (0.3 mg) Conjugated Estrogen Cream for Managing Atrophic Vaginitis - Nungruthai Sinnithithaworn; Lingling Salung; Somsak Pratipannawat (The Royal Thai College of Obstetricians and Gynaecologists, 2013)
Objectives:To evaluate efficacy and safety of low-dose conjugated estrogen cream (0.3 mg) for treatment of atrophic vaginitis in postmenopausal women.Methods and Methods: A double-blind, placebo-controlled, randomized trial was conducted during November 2012 and September 2013, involving 73 postmenopausal women with symptomatic atrophic vaginitis and vaginal maturation index (VMI) ≤ 55. Participants were randomly assigned to receive conjugated estrogen cream 0.3 mg or placebo twice a week for 12 weeks. The primary outcome was the change in the mean of VMI from baseline. Endometrial thickness was assessed by transvaginal sonography.Results:73 women were randomized into two group: 36 women in study group and 37 women in control group. All participants were completely follow up. Mean change of VMI in intervention group was significant higher than placebo group (34.5 ± 19.7 versus -0.6 ± 14.4, p<0.001). The mean change of VMI at 4 weeks was significantly higher in study group (21.2 ± 18.9 versus 1.3 ± 12.6, < 0.001). A significant greater reduction from baseline in vaginal pH at 12 weeks was shown in study group (-1.4 ± 1.0 versus -0.1 ± 0.9, p<0.001).Conclusions: Low-dose estrogen cream was superior to placebo in the mean change of VMI, decrease in vaginal pH and improved vaginal symptoms after 12 weeks of administration without increasing of endometrial thickness.